PUBLIC RELATIONS MANAGEMENT AS A MEANS OF STRENGTHENING THE BRANDING OF ISLAMIC EDUCATIONAL INSTITUTIONS - Susilo Surahman (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to analyze the role of public relations management (PR) as a strategic means in strengthening the branding of Islamic educational institutions in the midst of increasingly competitive competition from educational institutions. Strengthening branding is no longer understood as limited to the promotional aspect, but as a systematic process in building public image, reputation, and trust through planned, integrated, and sustainable communication. This research uses a qualitative approach with a case study design on one of the Islamic educational institutions that is actively developing public communication strategies. Data was collected through in-depth interviews, observations, and documentation studies, then it will be analyzed using interactive analysis techniques that included data reduction, data presentation, and conclusion drawn. The results of the study show that public relations management plays a significant role in building institutional identity, strengthening positioning, and increasing engagement with stakeholders through digital media and strategic partnership activities. The implementation of planning, organizing, implementing, and evaluating functions in public relations management has been proven to be able to increase the visibility of institutions and expand collaboration network trough internal communication, evaluation, and value-based branding. These findings confirm that professional and adaptive public relations management is an important instrument in supporting the competitiveness and sustainability of Islamic educational institutions in the era of digital transformation.